Hubungan perilaku menyikat gigi dengan status kebersihan gigi dan mulut PHPM (Personal Hygiene Performance-Modified) pada murid sekolah dasar - Ratna Wilis; Cut Ratna Keumala (Poltekkes Kemenkes Aceh, 2023)
Background: Oral health maintenance efforts should be conducted early in elementary school. The awareness and maintenance behavior of each individual is very important in maintaining oral hygiene. Oral health maintenance is instrumental in regular plaque control and removal. Preventive measures can be carried out routinely, such as brushing teeth, flossing, and dental examinations once every 6 months regularly to the dentist.Objectives: This study aimed to determine the relationship between tooth brushing behavior and oral hygiene status in elementary school students.Methods: This cross-sectional study was conducted at the State Elementary School of 50 Banda Aceh City in December 2022. The sample comprised 40 students. Collection through interviews and dental and oral examinations using diagnostic sets, disclosing fluids, and patient cards (KSP). Statistical analysis was performed using the chi-square test at a significance level of 95% CI.Results: Tooth brushing behavior among elementary school children was generally poor (57,5%), and oral hygiene was poor (47,5%). In addition, this study found a significant relationship between tooth brushing behavior and oral hygiene status (p = 0,007) in students from State Elementary School 50 in Banda Aceh City.Conclusion: Tooth brushing behavior had a significant relationship with oral hygiene status in students of State Elementary School 50 in Banda Aceh City. Suggestions for students to understand oral hygiene and how to brush their teeth properly.